Role of strategic and business planning in sustainable development of rural areas (on the example of depressed south- and northeastern regions of the Republic of Bashkortostan) - V. Ya. Akhmetov; G. I. Yakshimbetova (Вестник университета)
The article is devoted to the analysis of the role of strategic and business planning in the sustainable development of rural areas. Using the example of depressed and subsidised south- and north-eastern regions of the Republic of Bashkortostan, the authors focus on the relevance of developing effective strategies and business plans to overcome the social and economic problems characteristic of these territories. The paper examines methods and approaches to planning as well as their impact on improving the living conditions of the population, infrastructure development and sustainable agriculture. The problems hindering the development of these territories are clearly identified, and practical recommendations for authorities and local communities are proposed. The study highlights the expediency of creating a Monitoring Centre for Sustainable Rural Development under the Ministry of Agriculture of the Republic of Bashkortostan with the involvement of well-known scientists and experienced specialists, the importance of an integrated approach to planning that considers local characteristics and resources as well as actively involving the local population in decision-making processes. The article provides valuable conclusions and recommendations for specialists and researchers in the field of socio-economic development and rural management.